1991
DOI: 10.1001/archsurg.1991.01410330033004
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in Pregnancy

Abstract: A multicenter study involving three American College of Surgeons Level 1 trauma centers was undertaken to assess parameters that may predict fetal outcome. The records of 93 injured pregnant patients admitted from April 1, 1985, to March 31, 1990, were reviewed. There were three maternal deaths (3%) (mean Injury Severity Score, 43). Fourteen fetal/neonatal deaths (15%) occurred during the acute care admission period. Of these, eight were fetal deaths (two associated with maternal death), four were cases of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(23 citation statements)
references
References 33 publications
0
19
1
3
Order By: Relevance
“…The safety of the mother is one side of the story. The adverse effects of maternal head trauma and altered mental status for fetal viability have been shown previously (18, 27). Thus, the practice in this item should be cautious due to our knowledge gap.…”
Section: Discussionmentioning
confidence: 53%
“…The safety of the mother is one side of the story. The adverse effects of maternal head trauma and altered mental status for fetal viability have been shown previously (18, 27). Thus, the practice in this item should be cautious due to our knowledge gap.…”
Section: Discussionmentioning
confidence: 53%
“…The fetal loss rate of 7.9% observed was toward the range of 4-61% reported in other studies. [3810151819]…”
Section: Discussionmentioning
confidence: 99%
“…An ISS cut-off point of 9 was used because prior studies have reported its high sensitivity and specificity in predicting fetal death. [910]…”
Section: Methodsmentioning
confidence: 99%
“…1,2,3,4 Of the causes of trauma, motor vehicle accidents followed by domestic violence and falls are mostly responsible for abdominal injuries in pregnant women in compared to their nonpregnant counterparts. The immediate and long-term management of traumatic injury in pregnant women varies depending on the location and magnitude of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal heart rate should also be regularly monitored to specify how advanced pregnancy is and if the fetus would be viable if delivered. 1,2,3,4 …”
Section: Discussionmentioning
confidence: 99%